If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(-3a + 5) = 2y + 3 Reorder the terms: 2(5 + -3a) = 2y + 3 (5 * 2 + -3a * 2) = 2y + 3 (10 + -6a) = 2y + 3 Reorder the terms: 10 + -6a = 3 + 2y Solving 10 + -6a = 3 + 2y Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -6a = 3 + -10 + 2y Combine like terms: 10 + -10 = 0 0 + -6a = 3 + -10 + 2y -6a = 3 + -10 + 2y Combine like terms: 3 + -10 = -7 -6a = -7 + 2y Divide each side by '-6'. a = 1.166666667 + -0.3333333333y Simplifying a = 1.166666667 + -0.3333333333y
| 68=4v | | a(a^7+1)-7(a^7+1)=0 | | 4x-3=x-3+3x | | 3(4)-6+4+8=42 | | m+5=1 | | 12x-7=27x+3 | | -1x=13 | | 34a-4(5d+2)=36 | | 235=177-x | | -5n-15n=10 | | 6x-2=4x-(-2x+2) | | J=9(3.14)p | | 3x-3=2x-16 | | -5n-n=10 | | 3x-2=16-x^2 | | 185-u=252 | | 3x+5+6x=15 | | 14x+7-2=7 | | 11(y-2)=13(y+4) | | 3p^2+4p=8 | | 11T=8D+12pm | | 4(x+2)+3(2x-5)=31 | | (4x-25)+(3x-75)=180 | | 3-k=14 | | 6(4)+-25=7+-2(4) | | (8x+25)+(3x+75)=180 | | (2x-7)-(x-6)=14 | | 3x-3-24=4x-4 | | 2x-11=3x-7 | | y=16x+16+19 | | 1x-9=-27 | | 2+2=m |